PENGARUH METODE HYPNOTEACHING TERHADAP HASIL BELAJAR IPS KELAS IV UPT SDN 69 GALESONG I KABUPATEN TAKALAR - Kartika; Nursalam; Yumriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Kartika 2025. The Effect of Hypnoteaching Method on Social Studies Learning Outcomes of Grade IV Students of UPT Sdn 69 Galesong I, Takalar Regency. Thesis. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Supervisor I Prof. Dr. H. Nursalam, M.Si and supervisor II Dr. Yumriani, S.Pd, M.Pd.Based on the background, it explains that choosing the right learning method makes students more enthusiastic in learning so that it is expected to obtain maximum learning outcomes and provide a positive impact. Therefore, based on the background above, the researcher needs to conduct a study entitled "The Effect of Hypnoteaching Method on Social Studies Learning Outcomes of Grade IV Students of UPT SDN 69 Galesong 1, Takalar Regency. This research is an experimental study. Experiments are laboratory-based research. This type of experimental research method is part of the quantitative research method.Based on the research results, data analysis, and discussion outlined in the previous chapter, it can be concluded that the hypnoteaching method has an effect on the social studies learning outcomes of Grade IV students at UPT SDN 69 Galesong I, Takalar Regency. The descriptive statistical data analysis shows that the mean (average value) of the students' pretest results before treatment was 63.03. Meanwhile, after treatment using the hypnoteaching method, students' posttest scores increased to 81.97. After conducting a normality test using the Kolmogorov- Smirnov test, the data met the assumption of normality, as the significance value for the pretest was 0.127 > 0.05, and for the posttest, 0.109 > 0.05. This indicates that the data were normally distributed. The results of the hypothesis test using the T-Test also showed a 2-tailed sig. value of 0.000 for both the pretest and posttest. Furthermore, an N-Gain test was conducted on the students' pretest and posttest results to determine the effectiveness of the hypnoteaching method. The N-Gain score was 0.18, classified as quite effective. Therefore, it was concluded that H0 was rejected and H1 was accepted, stating that the hypnoteaching method had an effect on the social studies learning outcomes of Grade IV students at UPT SDN 69 Galesong I, Takalar Regency.